Peningkatan Pemahaman Kontekstual Bacaan Siswa Kelas IV Melalui Model Literasi Interaktif Berbasis Proyek di Sekolah SD Marga Jaya Suoh Lampung Barat - Enjel Supanti; Evi Gusliana (Civiliza Publishing, Indonesia., 2026)
The low ability of students to understand reading contextually is the main obstacle in basic literacy in rural areas, where students tend to read texts mechanically without being able to relate them to the reality of daily life. This study aims to improve the contextual understanding of reading of grade IV students of SD Marga Jaya Suoh, West Lampung, through the application of the Project-Based Interactive Literacy Model. The research method used was a collaborative Classroom Action Research (PTK) of the Kemmis and McTaggart models which was carried out in two cycles on 28 students. Data collection techniques included activity observation, learning outcome tests, and authentic project documentation. The research findings showed a significant increase in each cycle; in the pre-stratus condition, the average student score was only 64.28 with classical completeness of 35%. After being given action, the average score increased to 72.14 in Cycle I, and jumped sharply to 84.50 at the end of Cycle II with classical completeness reaching 89%. This success was triggered by the integration of Suoh's local wisdom into the